Timing and Holistic Measure of Sexual Function in Patients with IBD After Proctectomy - Byrd, Tamara; Roth Bayer, Carey (Turkish Journal of Gastroenterology, 2021)
Cite this article as: Byrd T, Bayer C. Timing and holistic measure of sexual function in patients with IBD after proctectomy. Turk J Gastroenterol. 2021; 32(1): 111-112.